2009
DOI: 10.1111/j.1600-0838.2009.00932.x
|View full text |Cite
|
Sign up to set email alerts
|

Lateral ankle sprain alters postural control in bipedal stance: Part 2 sensorial and mechanical effects induced by wearing an ankle orthosis

Abstract: To investigate the effects induced by wearing an orthosis during the rehabilitation process, 23 ankle sprain patients (degrees I and II) were evaluated in three conditions (reference, with an elastic compression stocking and with an orthosis), 14 h, 10 and 30 days on average after their injury and compared with those of 30 age-matched healthy individuals. The patients were tested with separate measurements of the reaction forces under each limb to highlight the possible compensatory mechanisms between the soun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Five studies (WGSS = 1; TMSS = 3; SRSS = 1) concluded the findings with a neutral statement [61,6770]. A study from WGSS reported mixed results, where they only found the beneficial effects in under specific constraints, including an eyes-closed condition [28]; and under a stability task performed by participants on an injured leg [22,23,25]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Five studies (WGSS = 1; TMSS = 3; SRSS = 1) concluded the findings with a neutral statement [61,6770]. A study from WGSS reported mixed results, where they only found the beneficial effects in under specific constraints, including an eyes-closed condition [28]; and under a stability task performed by participants on an injured leg [22,23,25]. …”
Section: Resultsmentioning
confidence: 99%
“…Following these promising findings, a number of research programmes have since examined the utility of different approaches for achieving improved performance outcomes, ostensibly via similar mechanisms. Such interventions have included: tapes [1921], braces [2224] and compression garments [2527] in young, healthy adults and people with lower-limb injuries (e.g., Functional Ankle Instability (FAI)).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In more challenging conditions involving visual occlusion, compression garments (shorts) improved the total time in unipedal standing balance [21]. For young athletes with lower extremity injuries, studies have shown that compression via orthoses and sleeves improved uni -and bi-pedal balance performance [2,10,19,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…These studies have mainly investigated immediate (perhaps temporary) effects of wearing compression garments in elite athletic samples. For example, such research has investigated elite alpine skiers [32], female athletes [21], and young athletes with lower limb injuries [2,10,23,38]. Investigations on the impact of wearing compression garments, such as socks, on proprioception to regulate motor performance have been infrequent, with non-athletic samples.…”
Section: Introductionmentioning
confidence: 99%